Efektivitas Analisis Beban Kerja Berbasis Elektronik (E-ABK) di Dinas Perumahan Rakyat dan Kawasan Pemukiman serta Pertanahan Kota Surabaya - Zikra, Rabbiul; Anysakurillah, Rosyidatuzahro (IAI Nasional Laa Roiba Bogor, 2024)
In the Minister of State Apparatus Empowerment and Bureaucratic Reform Regulation Number 1 of 2020 concerning Guidelines for Job Analysis and Workload Analysis, workload analysis is defined as a process of collecting, recording, processing and compiling job data into job information. According to Hasibuan,